Chemotaxis of bone marrow derived eosinophils in vivo: A novel method to explore receptor‐dependent trafficking in the mouse. Issue 8 (14th June 2013) - Sturm, Eva M.; Dyer, Kimberly D.; Percopo, Caroline M.; Heinemann, Akos; Rosenberg, Helene F.
<x xml:space="preserve">Abstract</x> Here, we describe a novel method via which ex vivo cultured mouse bone marrow derived eosinophils (bmEos) can be adoptively transferred into recipient mice in order to study receptor‐dependent recruitment to lung tissue in vivo. Intratracheal instillation of recombinant human eotaxin‐2 (hCCL24) prior to introduction of bmEos via tail vein injection resulted in an approximately fourfold increase in Siglec F‐positive/CD11c‐negative eosinophils in the lungs of eosinophil‐deficient ΔdblGATA recipient mice compared with controls. As anticipated, bmEos generated from CCR3‐gene‐deleted mice did not migrate to the lung in response to hCCL24 in this model, indicating specific receptor dependence. BmEos generated from GFP‐positive BALB/c mice responded similarly to hCCL24 in vitro and were detected in lung tissue of BALB/c WT as well as BALB/c ΔdblGATA eosinophil‐deficient recipient mice, at approximately fourfold (at 5 h post‐injection) and approximately threefold (at 24 h postinjection) over baseline, respectively. Comparable results were obtained with GFP‐positive C57BL/6 bmEos responding to intratracheal hCCL24 in C57BL/6 ΔdblGATA recipient mice. The use of ex vivo cultured bmEos via one or more of these methods offers the possibility of manipulating bmEos prior to transfer into a WT or gene‐deleted recipient host. Thus, this chemotaxis model represents a novel and robust tool for pharmacological studies in vivo.